Fire performance analysis for buildings - Fitzgerald, Robert W.; Meacham, Brian J. (Wiley, 2017)
Fire Performance Analysis for Buildings, 2nd Edition has been completely restructured around a performance based framework. Applications integrate traditional fire defenses with fire science and engineering to combine component performance with holistic performance.
Revised edition of: Building fire performance analysis. 2004.
Includes index.
Keywords: Building, Fireproof.; Fire prevention -- Inspection.; elektronické knihy; electronic books